Risk and Protective Factors of Anxiety in Nurses During the COVID-19 Pandemic: A Systematic Review - Eka Wahyuni, Sri; Budi Anna Keliat; Herni Susanti; Besral (Talenta Publisher, 2024)
The COVID-19 pandemic has significantly impacted nurses, exposing them to challenges that have affected their overall well-being. Most nurses have experienced psychosocial problems, including anxiety. This study aims to identify the protective and risk factors associated with anxiety among nurses during the COVID-19 pandemic. A systematic review was used as a method in this study. Eight databases were used Science Direct, PubMed, CINAHL, Embase, ProQuest, Scopus, Taylor & Francis, and JSTOR. The literature search was conducted using keywords derived from the Medical Subject Headings (MeSH) framework. The search terms included: Nurses OR